Dietary Regulation of Gut-Brain Axis in Alzheimer’s Disease: Importance of Microbiota Metabolites - Frausto, Dulce M.; Forsyth, Christopher B.; Keshavarzian, Ali; Voigt, Robin M. (Frontiers in Neuroscience, 2021)
Alzheimer’s disease (AD) is a neurodegenerative disease that impacts 45 million people worldwide and is ranked as the 6th top cause of death among all adults by the Centers for Disease Control and Prevention. While genetics is an important risk factor for the development of AD, environment and lifestyle are also contributing risk factors. One such environmental factor is diet, which has emerged as a key influencer of AD development/progression as well as cognition. Diets containing large quantities of saturated/trans-fats, refined carbohydrates, limited intake of fiber, and alcohol are associated with cognitive dysfunction while conversely diets low in saturated/trans-fats (i.e., bad fats), high mono/polyunsaturated fats (i.e., good fats), high in fiber and polyphenols are associated with better cognitive function and memory in both humans and animal models. Mechanistically, this could be the direct consequence of dietary components (lipids, vitamins, polyphenols) on the brain, but other mechanisms are also likely to be important. Diet is considered to be the single greatest factor influencing the intestinal microbiome. Diet robustly influences the types and function of micro-organisms (called microbiota) that reside in the gastrointestinal tract. Availability of different types of nutrients (from the diet) will favor or disfavor the abundance and function of certain groups of microbiota. Microbiota are highly metabolically active and produce many metabolites and other factors that can affect the brain including cognition and the development and clinical progression of AD. This review summarizes data to support a model in which microbiota metabolites influence brain function and AD.